2018
DOI: 10.1101/330068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular definition of group 1 innate lymphoid cells in the mouse uterus

Abstract: Determining the function of uterine lymphocytes is challenging because of the rapidly changing nature of the organ in response to sex hormones and, during pregnancy, to the invading fetal trophoblast cells. Here we provide the first genome-wide transcriptome atlas of mouse uterine group 1 innate lymphoid cells (g1 ILCs) at mid-gestation. The composition of g1 ILCs fluctuates throughout reproductive life, with Eomes-veCD49a+ ILC1s dominating before puberty and specifically expanding in second pregnancies, when … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 79 publications
(100 reference statements)
2
25
0
Order By: Relevance
“…There are three murine Group 1 ILC subsets: CD49a+Eomes-uterine ILC1 (uILC1), CD49a+Eomes +trNK and CD49a-Eomes+conventional NK (cNK) 4,46,47 . Murine uILC1 express CXCR6 and may represent memory cells as they expand in second pregnancies 46 . They therefore could be functionally analogous to KIR+PTdNK, although they have low levels of Ly49.…”
Section: Discussionmentioning
confidence: 99%
“…There are three murine Group 1 ILC subsets: CD49a+Eomes-uterine ILC1 (uILC1), CD49a+Eomes +trNK and CD49a-Eomes+conventional NK (cNK) 4,46,47 . Murine uILC1 express CXCR6 and may represent memory cells as they expand in second pregnancies 46 . They therefore could be functionally analogous to KIR+PTdNK, although they have low levels of Ly49.…”
Section: Discussionmentioning
confidence: 99%
“…57 When heterogeneity of c-Kit + CD24 + NK cells were assessed through tSNE analysis of flow cytometry data, c-Kit + CD24 + NK cells were a quite homogeneous cell population in expression of NK cell markers. Although some of c-Kit + CD24 + NK cells dimly expressed several myeloid cell markers, it has previously been reported that NK cells express several myeloid cell markers, [57][58][59][60][61][62] suggesting that c-Kit + CD24 + NK cells are a homogeneous NK cell population with heterogeneity of several myeloid cell markers. To further investigate these issues of identity and heterogeneity of c-Kit + CD24 + NK cells, high dimensional single-cell analysis such as single-cell RNA sequencing or mass cytometry will be required.…”
Section: Discussionmentioning
confidence: 95%
“…17,20 The alymphoid Rag2 −/− Il2rg −/− mice dams express less Spp1, indicating lymphocytes are an important source of OPN. 35 Activated Kupffer cells contribute to hepatic IR in obese mice. 36 Kupffer cells and macrophage-derived OPN, and the subsequent effect of OPN on these cells in the liver warrant further attention in future studies.…”
Section: Discussionmentioning
confidence: 99%